FREQUENCY OF GALL BLADDER CARCINOMA IN PATIENTS WITH ACUTE AND CHRONIC CHOLECYSTITIS - Haq, Najamul; Khan, Basharat Ali; Imran, Muhammad; Akram, Adeel; Jamal, Abdul Basit; Bangash, Fatima (Journal of Ayub Medical College Abbottabad, 2014)
Background: Gallbladder carcinoma is a relatively uncommon neoplasm which is more common in the seventh decade of life compared to that of cholelithiasis which is in the fourth decade. The objective of the study was to determine the frequency of carcinoma gall bladder in cases of acute and chronic cholecystitis particularly with reference to cholelithiasis. Methods: This cross-sectional observational study was done in the department of Surgery at Fauji Foundation Hospital, Rawalpindi from 1stJanuary, 2009 till 31stOctober, 2011. All 310 cholecystectomies performed during this period were included in this study. The specimens collected were macroscopically examined and sent for histopathology. All the reports were reviewed and the results recorded. Results: Out of 310 cases, 27 (8.7%) had acute cholecystitis and 280 (91.2%) were chronic cholecystitis. 3 specimens got autolysed and therefore excluded from the study. 290 cases had cholelithiasis. 2 out of 290 calculous cases were found to have coexistent carcinoma gall bladder proven on histopathology. Conclusion: Frequency of carcinoma gallbladder associated with cholelithiasis discovered incidentally after cholecystectomy is very low in our patients. Keywords: Cholelithiasis, carcinoma gallbladder, histopathology, cholecystitis